PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK ISLAMI UNTUK MENINGKATKAN HASIL BELAJAR SISWA MADRASAH IBTIDAIYAH NEGERI (MIN) DI KOTA BANDA ACEH - Rafidhah Hanum; Irwandi Irwandi; Raihatul Miska (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
Islamic Comic Learning Media is a media or tool developed to improve student learning outcomes. Comic media can be used in a two-way learning process, namely as a teaching aid and learning media that can be used by students themselves. The results of initial observations show that there is still limited media used in the learning process at MIN MIN 7 Banda Aceh, especially classes in class V. The objectives of this research are 1) To determine the process of developing Islamic Comics media to improve the learning outcomes of class V students at MIN 7 Banda Aceh, 2) To determine the feasibility of the Islamic Comic media being developed to improve the learning outcomes of class V students at MIN 7 Banda Aceh. The research method used is research and development (R&D) and uses the Borg and Gall theory through 7 stages. Data collection was carried out through a validation process and product testing. The result of this research was that the development of Islamic comic media was said to be suitable for use. This is based on the assessment that comic media as a whole has been declared feasible with a percentage result of 92.69% and can improve student learning outcomes at MIN 7 Banda Aceh based on the product test analysis obtained, namely tcount = while ttable = 1.711. So it can be concluded that tcount > ttable, which means H1 is accepted and H0 is rejected. This shows that students' final abilities are better than before using Islamic comic learning media.Keywords: Islamic Comic Media, Learning Results